Funkcje realizmu w fantastyce dla młodego czytelnika - Wróblewski, Maciej (Poznańskie Studia Polonistyczne. Seria Literacka, 2017)
In the article the author examines fantastic novels by contemporary Polish writers (Andrzej Maleszka, Paweł Beręsowicz, Rafał Kosik and other) for young readers in a cultural context. In his essay he uses two well-known cultural categories “myth” and “magic” to his analysis of fantastic novels. According to the author, the myth and magic have two important functions in fantastic children’s literature. First, they lead young readers to knowledge about the world and depict different, complex phenomena of cultural dimension. Second, the myth and magic create a particular space (what “engulfs” young readers) of play and entertainment. Moreover, the myth and magic attract young readers to fabulous worlds including the elements of realistic literary convention. Thereby the writers increase their credibility among the youth. A “myth-magic” in the presented word of contemporary Polish fantastic novels assures balance between incredible entertainment represented by wizards, witches, dragons and the real world with characters having various digital devices within reach.